2009
DOI: 10.1002/cbic.200800623
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline Nanorods as Possible Templates for the Synthesis of Amorphous Biosilica during Spicule Formation in Demospongiae

Abstract: High-resolution microscopy shows that, during the initial stages of demosponge spicule formation, a primordial crystalline structure is formed within the axial filament. The recently developed electron diffraction tomography technique reveals that the nanorods have a layered structure that matches smectitic phyllosilicates. These intracellular nanorods have been considered as precursors of mature spicules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…Morphological studies were performed by Philips EM420. Linescan and spot EDX were performed in scanning transmission electron microscopy (STEM) mode by a FEI Tecnai F30 equipped with an energy-dispersive X-ray spectrometer (Mugnaioli et al, 2009). …”
Section: Transmission Electron Microscopy and Energy-dispersive X-raymentioning
confidence: 99%
“…Morphological studies were performed by Philips EM420. Linescan and spot EDX were performed in scanning transmission electron microscopy (STEM) mode by a FEI Tecnai F30 equipped with an energy-dispersive X-ray spectrometer (Mugnaioli et al, 2009). …”
Section: Transmission Electron Microscopy and Energy-dispersive X-raymentioning
confidence: 99%
“…Interestingly, multimetallic silicate crystals have been identified in natural sponge biosilica (26), suggesting that recombinant silicatein activity in these in vitro mineralization vesicles exhibits this natural activity as well. Our results from genetic screening showed that this crystal-forming ability could be (re)acquired via evolutionary selection for expression in a range of in vitro environments.…”
Section: Discussionmentioning
confidence: 95%
“…During in vivo formation of spicules (sponge skeletal elements; Fig. 1A), silicatein protein filaments are initially assembled intracellularly before being exported to an extracellular vesicular compartment (26,28,31). In both the in vivo and in vitro processes, silicatein enzymatically hydrolyzes precursor molecules to initiate mineralization at the silicatein filament (or silicatein-bead) surface; mineralization is templated along the silicatein scaffold, and the mineral grows radially from the scaffold surface within a shape-constraining compartment as the templating polymer becomes axially occluded within a spicule (23,28) (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations